Tafsir Ta’wil: Penafsiran Ulang Relasi Suami Istri dalam Al Qur’an - Ruslan, Mohammad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This research purposes to reinterpret relation between husband and wife in the Qur’an. It is focused at verse that is frequently understood misogynistic namely QS al-Nisā: 34. The understanding is caused by using the literalistic-legalistic approach. In this research, the writer uses different approach namely thesocio-historicalapproach. It requiresfour-stepnamely: (1)step ofen counter with text (2)stepofcriticalanalysisstep, (3)stepof meaning for the first recipients, 4) step of meaning for the contemporary context. The result of this research is that the concept of a husband’s leadership for wife at this time is. It is built above a patriarchal worldview, perilous country, and employment that requires effort and power. In this situation, the women are in low position and debt of gratitude to men till the Qur’an appropriates this condition. Contemporary reality does not indicate situation like that so the relation between husband and wife is more appropriate as a partnership.